Peran Pustakawan dalam Peningkatan Literasi Anak Sekolah Melalui Layanan Mobile Library pada Dinas Perpustakaan Kota Padang - Nofita Sari, Shinta (UIN Imam Bonjol Padang, 2023)
This research was conducted on the Mobile Library service at the Padang City Library. This study aims to determine the role of librarians in increasing school children's literacy through the Mobile Library service at the Padang City Library Service. The research method used is descriptive qualitative. The results of this study indicate that 1) Story Telling aims to increase school children's interest in reading and loving books, 2) Read Aloud aims to teach effective reading for school children so that they can condition children's brains to read as a fun activity, 3) Information Services can be utilized by school children which aim to assist the process of activities in identifying information sources in answering and responding to a particular question given by the librarian and school children can borrow collections from the librarian.